Harmonizing Diversity: Reviewing Multicultural Awareness and Political Policy - Ketaren, Amiruddin; Ilham, Iromi; Rangkuty, Rakhmadsyah Putra; Husen, M.; Maliati, Nulwita (Malikussaleh Social and Political Reviews, 2023)
A multicultural society is an intricate social construct with diverse components, including ethnicity, religion, and race, which engage in social interactions that mutually impact one another. Nevertheless, minority groups frequently find themselves in a precarious and subjugated state. The prevalence of majority dominance frequently leads to repressive actions, subsequently provoking resistance from minority factions and even escalating into violent conflicts. This article aims to seek novel strategies for governing pluralistic communities, emphasizing the significance of multicultural consciousness as the fundamental basis for formulating comprehensive and equitable policies. To effectively navigate the intricacies of ethnic interactions, it is essential to implement policies and activities that prioritize justice, autonomy, and shared accountability. To achieve a harmonious multicultural society, it is necessary to reorganize government institutions and create an atmosphere that values, appreciates, and incorporates multiple identities, hence promoting fairness and equality. This article suggests developing an enhanced framework for effectively managing social conflict and fostering harmony in a diverse society.